Pathogenic Potential to Humans of Bovine Escherichia coli O26, Scotland - Margo E. Chase-Topping; Tracy Rosser; Lesley J. Allison; Emily Courcier; Judith Evans; Iain J. McKendrick; Michael C. Pearce; Ian Handel; Alfredo Caprioli; Helge Karch; Mary F. Hanson; Kevin G.J. Pollock; et al. (Emerging Infectious Diseases, 2012)
Escherichia coli O26 and O157 have similar overall prevalences in cattle in Scotland, but in humans, Shiga toxin–producing E. coli O26 infections are fewer and clinically less severe than E. coli O157 infections. To investigate this discrepancy, we genotyped E. coli O26 isolates from cattle and humans in Scotland and continental Europe. The genetic background of some strains from Scotland was closely related to that of strains causing severe infections in Europe. Nonmetric multidimensional scaling found an association between hemolytic uremic syndrome (HUS) and multilocus sequence type 21 strains and confirmed the role of stx2 in severe human disease. Although the prevalences of E. coli O26 and O157 on cattle farms in Scotland are equivalent, prevalence of more virulent strains is low, reducing human infection risk. However, new data on E. coli O26–associated HUS in humans highlight the need for surveillance of non-O157 enterohemorrhagic E. coli and for understanding stx2 phage acquisition.